1993
DOI: 10.1002/bjs.1800801119
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure in patients undergoing transhiatal or transthoracic oesophagectomy for carcinoma of the thoracic oesophagus

Abstract: Resting energy expenditure (REE) was studied in five patients undergoing transhiatal and in 14 undergoing transthoracic oesophagectomy for carcinoma. All resections were performed with an intention to cure. REE was measured by indirect calorimetry before operation and on days 1, 3, 5 and 7 after surgery. Following transthoracic oesophagectomy, REE increased significantly on days 1, 3, 5 and 7 after operation, and on day 7 the value was significantly higher (P < 0.05) than that obtained after transhiatal surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Sato et al (18,19) showed a 31% increase in the mREE in patients undergoing an esophagectomy. However, the increased rate in the mREE in our patients was lower than that from previous studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sato et al (18,19) showed a 31% increase in the mREE in patients undergoing an esophagectomy. However, the increased rate in the mREE in our patients was lower than that from previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…(20) Although one would be more likely to find stress-induced hypermetabolism on earlier postoperative days, the increase in the mREE of patients undergoing a transhiatal or transthoracic esophagectomy was almost the same as during the first seven days. (18) …”
Section: Discussionmentioning
confidence: 99%
“…Limiting surgical stress for patients with significant medical comorbidity is clearly desirable. Indeed it has been shown that energy expenditure is significantly lower following TH when compared to TT, 24 although this may arguably be a function of the shorter operating time necessary for a TH approach.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several operative procedures, such as esophagectomy via transhiatal, right and left thoracotomy, have also been included in these study populations, although surgical stress and the rate of postoperative morbidity and mortality differ between the transthoracic approach with one‐lung ventilation and the transhiatal approach …”
Section: Introductionmentioning
confidence: 99%